2018
DOI: 10.1111/acel.12716
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell Immunoglobulin and ITIM Domain Contributes to CD8+ T‐cell Immunosenescence

Abstract: SummaryAging is associated with immune dysfunction, especially T‐cell defects, which result in increased susceptibility to various diseases. Previous studies showed that T cells from aged mice express multiple inhibitory receptors, providing evidence of the relationship between T‐cell exhaustion and T‐cell senescence. In this study, we showed that T‐cell immunoglobulin and immunoreceptor tyrosine‐based inhibitory motif (ITIM) domain (TIGIT), a novel co‐inhibitory receptor, was upregulated in CD8+ T cells of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 48 publications
9
76
0
Order By: Relevance
“…Although TEMRA cells have been shown to display some features of cellular senescence, such as increased DNA damage, as well as reduced proliferative capacity, telomere lengths, and telomerase activity (28,29), it remains unclear whether they can be defined as senescent in the classical sense, particularly as TEMRA cells retain function and their growth arrest is reversible (6,20). In line with previous studies (19), we observed that the fraction of CD8+ TEM, and TEMRA cells were significantly more abundant in old donors compared to young donors or cord blood, while the fraction of TN cells wasdramatically decreased with age ( Fig. 4A and Fig.…”
Section: Cd8+ T Cells Increasingly Undergo Cellular Senescence With Asupporting
confidence: 71%
See 1 more Smart Citation
“…Although TEMRA cells have been shown to display some features of cellular senescence, such as increased DNA damage, as well as reduced proliferative capacity, telomere lengths, and telomerase activity (28,29), it remains unclear whether they can be defined as senescent in the classical sense, particularly as TEMRA cells retain function and their growth arrest is reversible (6,20). In line with previous studies (19), we observed that the fraction of CD8+ TEM, and TEMRA cells were significantly more abundant in old donors compared to young donors or cord blood, while the fraction of TN cells wasdramatically decreased with age ( Fig. 4A and Fig.…”
Section: Cd8+ T Cells Increasingly Undergo Cellular Senescence With Asupporting
confidence: 71%
“…Although subsets of PBMCs, such as cytotoxic CD8+ T cells undergo replicative senescence in culture, whether and to what degree they do so also in vivo remains unclear (7,18). A primary reason for this uncertainty is that specific markers used to identify senescent CD8+ T cells in the past (19,20), such as a loss of the cell surface receptors CD28 and CD27 and a gain of expression of CD45RA, CD57, TIGIT and/or KLRG1 do not accurately characterize all T cells that have permanently lost the ability to proliferate due to acquisition of macromolecular damage, upregulation of cyclin-dependent kinase (CDK) inhibitors, and development of senescence associated ß-Galactosidase (SA-ßGal), criteria that define the state of cellular senescence (16). In fact, CD8+ T cells that have lost expression of CD28 and/or that display varying levels of CD45RA, CD57, TIGIT or KLRG1 maintain the ability to proliferate following appropriate stimulation, which is incompatible with a classical senescence response (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Since ANG II/AT-1R signaling triggers immune exhaustion, older COVID-19 patients may present with more complex immune defects engendered by the simultaneous expression of exhaustion and senescence markers (104). Indeed, novel preclinical studies have demonstrated that TIGIT knockdown can reverse premature cellular and immune aging, suggesting that downregulation of this molecule may benefit COVID-19 patients (105).…”
Section: Older Individuals and Covid-19 Critical Illnessmentioning
confidence: 99%
“…often a late-stage complication of AT, so prolonged disease duration may play a role in AT as well [33]. In support, there is evidence of age contributing to the variance of TIGIT expression [34], a feature shared with several other IR showing upregulation in aged T cell populations. Lastly, inflammatory injury and TSH stimulation have been both associated with thyroid carcinoma in AT [35,36]; here, we noticed that both these factors might be linked to a prototypical cancer immunity cycle-associated IR, TIGIT [37].…”
Section: Discussionmentioning
confidence: 92%